Megabulbus in endoscopy; suspect for superior mesenteric artery syndrome in children - Eğritaş, Ödül; Demiroğullari, Billur; Dalgıç, Buket (Turkish Journal of Gastroenterology, 2015)
Abstract Rarity of Superior Mesenteric Artery Syndrome (SMAS) and necessity of invasive tests to verify the diagnosis leads to patients receiving symptom-oriented drugs for a long period without any definite diagnosis. Diagnostic tests such as barium series, abdominal CT scan, abdominal angiography or magnetic resonance arteriography are used in patients with suspected SMAS. In pediatric patients, a non-invasive SMAS diagnosis may be considered easily with abdominal ultrasound performed by experienced hands. Megabulbus is used as a radiological term; however, reviewing the literature an endoscopic definition for megabulbus was not found. We decided to mention severely dilated pyloric ring and bulb as megabulbus. Megabulbus might be an indicator for SMAS. This is the first case of SMAS in adult and pediatric age groups presenting with megabulbus.